Siliciclastic and bioclastic contouritic sands: Textural and geochemical characterisation. (June 2021) - de Castro, S.; Miramontes, E.; Dorador, J.; Jouet, G.; Cattaneo, A.; Rodríguez-Tovar, F.J.; Hernández-Molina, F.J.
Abstract: The purpose of this study is to differentiate and characterise contouritic sands in two different locations with variable sediment compositions (siliciclastic and bioclastic) based on a multiproxy approach that includes the analysis of sedimentary texture, semi-quantitative geochemistry, microfacies and ichnological information, as well as a Principal Component Analysis (PCA) applied to geochemical and sedimentary data on sediment cores. The integration of sedimentological analyses and the PCA permits also to the differentiation between fine-grained deep-water deposits such as hemipelagites, muddy contourites and hyperpycnites. A depositional model is proposed here, based on geochemical and sedimentological characteristics of the Holocene-highstand Mozambique Channel upper slope sands, and glacial-lowstand Corsica Contourite Depositional System middle slope sands. The upper continental slope of the Mozambican margin is characterised by siliciclastic sandy contourites, muddy contourites and muddy hyperpycnites. Mozambique siliciclastic sandy contourites constitute large accumulations of well-sorted very fine to coarse sand with evidences of strong winnowing and reworking under high-energy conditions. The sedimentary facies represents highstand contourite sands and shows a reversely-graded trend. The contourite drift on the Pianosa ridge (eastern flank of the Corsica Trough) consists of bioclastic sandy and muddy contourites and hemipelagites. Bioclastic sandy contourites are made up of shallow-marine winnowed bioclasts with a reversely- and normally-graded trend and represent lowstand contourite sands. The PCA in the two environments —showing a distinctive geochemical signal— allows for differentiation of the contourite deposits. In siliciclastic sands, reworking is marked by an accumulation of Si, Zr, and Sr in fine- to medium-grained sands. In bioclastic sands, reworking is less evident but it is characterised by accumulations of Ca and Sr. The reworking and winnowing bottom current effects are also observed at the microfacies scale. Both types of contourite deposits show evidences of intermittent depositional conditions depending on the ichnodiversity, distribution and abundance of trace fossils. This work is useful to discriminate similar fine-grained deposits in different continental margins which would contribute to a better understanding of sedimentary deposits and processes in deep-marine environments. Graphical abstract: Image 1 Highlights: Reworking proxies are different for bioclastic and siliciclastic sands. Winnowing and reworking proxies have a distinctive geochemical signal and they are supported at the microfacies scale. Bi-gradational contourite sequence show evidences of intermittent depositional conditions. Sediment input and distance to sediment source has a strong impact on the bi-gradational contourite sequence formation. Contourite drifts are not only formed by contourite deposits.